If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -7)(4x + -7) = 0 Reorder the terms: (-7 + 2x)(4x + -7) = 0 Reorder the terms: (-7 + 2x)(-7 + 4x) = 0 Multiply (-7 + 2x) * (-7 + 4x) (-7(-7 + 4x) + 2x * (-7 + 4x)) = 0 ((-7 * -7 + 4x * -7) + 2x * (-7 + 4x)) = 0 ((49 + -28x) + 2x * (-7 + 4x)) = 0 (49 + -28x + (-7 * 2x + 4x * 2x)) = 0 (49 + -28x + (-14x + 8x2)) = 0 Combine like terms: -28x + -14x = -42x (49 + -42x + 8x2) = 0 Solving 49 + -42x + 8x2 = 0 Solving for variable 'x'. Factor a trinomial. (7 + -4x)(7 + -2x) = 0Subproblem 1
Set the factor '(7 + -4x)' equal to zero and attempt to solve: Simplifying 7 + -4x = 0 Solving 7 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -4x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -4x = 0 + -7 -4x = 0 + -7 Combine like terms: 0 + -7 = -7 -4x = -7 Divide each side by '-4'. x = 1.75 Simplifying x = 1.75Subproblem 2
Set the factor '(7 + -2x)' equal to zero and attempt to solve: Simplifying 7 + -2x = 0 Solving 7 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -2x = 0 + -7 -2x = 0 + -7 Combine like terms: 0 + -7 = -7 -2x = -7 Divide each side by '-2'. x = 3.5 Simplifying x = 3.5Solution
x = {1.75, 3.5}
| 36-y=201 | | 6k-5p=2 | | -1/2-6+2 | | X*15+25=x*5+115 | | (3/5x)+(1/3x)=x-6 | | 3/5x=-18 | | 16+2x=2x+4 | | 7r=3r-52 | | 41/4-15/6 | | 2x+88=0 | | 4x+12=7x-9 | | 7p-11=8p-5 | | 3/8+24/8 | | Y=40x+50 | | 1.5+w=9 | | x^3-6x-72x=0 | | 38=24-7+5x | | 1/2q=50 | | 1/9x=600000 | | x=5(3/x-5) | | 8(p)-(7)=75 | | 8+4(5x-5)=6-5(2x+1) | | s=5(3/r-5) | | 7=2x+x+7 | | Z=M+Mrf | | 10x-4x=43 | | 7/10x38/100 | | 2x+7=x-4 | | -3x+5+x=-17 | | 0.5p-0.06+0.6p=0.27 | | 4x^2=28x+49 | | x=y^2-4y |